Młodzieżowe organy konsultacyjne samorządu terytorialnego - Mędrzycki, Radosław (Kwartalnik Prawa Publicznego, 2015)
The article consists of an analysis of regulations concerning the formation of youth consultative bodies in local self-government. The investigated issue is crucial from the perspective of supporting and spreading of the self-governance ideas among the youth, including the development of civic attitudes among the adolescent citizens. The youth consultative bodies are briefly regulated by the Polish legal system, and their establishment relies solely on the gmina self-government act (Ustawa o Samorządzie Gminnym). However, such organs are also present in other self-government units: voivodeships and powiats. The current regulation limits the nature of the youth municipal council (młodzieżowa rada gminy) to the role of a consultative body. The inner structure and procedures regarding the election of members of youth municipal council are in sole control of the municipal council (rada gminy), although this control is limited by the municipal council statute which results from the state regulatory acts .